LOVE AND BELONGING NEEDS OF SAYURI IN MEMOIRS OF A GEISHA MOVIE: A HUMANISTIC PSYCHOLOGICAL APPROACH - HERAWANI, MEIRNA ADITIA (2011)
This study describes the hierarchy of needs of Sayuri viewed from humanistic perspective, and analyzes the Memoirs of a Geisha movie based on its structural elements. The research is conducted by using qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data source. The primary data is Memoirs of a Geisha movie directed by Rob Marshall. The secondary data source are the books about psychology and the other sources, which are related to the analysis. The method of collecting data is observation and library review. Based on the analysis, the study reveals there are some motives underlying the struggle of Sayuri. The motives are getting a better life, respected by others, and the last motive is to get her beloved. The hierarchy needs of Sayuri are fulfilled enough, with the help of her relation, such as her big sister. Her physiological needs could fulfill enough when she becomes a maid in the okiya house, but she could not get safety and security needs because she got bad treatment. She can fulfilled safety and security needs when she was adopted by Mameha. She also fulfilled self-esteem needs and self-actualization needs with the help of Mameha and Iwamura. After she could fulfill those four needs, she determined to get her love to fulfilled love and belonging needs.